2004
DOI: 10.1002/ajh.20090
|View full text |Cite
|
Sign up to set email alerts
|

Desferrioxamine related maculopathy: A case report

Abstract: Desferrioxamine is used for the treatment of chronic iron overload, acute iron poisoning, and certain anaemias. Ocular toxicity secondary to prolonged treatment with desferrioxamine may result in night blindness, visual field constriction, cataract, pigmentary retinopathy and optic neuropathy. To avoid such complications an ophthalmic screening has been suggested for patients taking desferrioxamine. We report an 81-year-old patient who developed irreversible ocular toxicity despite undergoing ophthalmic screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 14 publications
(12 reference statements)
0
15
0
1
Order By: Relevance
“…6 On fundus examination, multiple discrete hypopigmented circular lesions over the posterior pole, the midperipheral retina, or around the optic disk were observed associated to multiple confluent hyperreflective deposits on SD-OCT in the different layers: RPE, the ellipsoid zone, and choroid. [6][7][8][9][10] Deferoxamine retinopathy and our case share some similarities: the RPE depigmentation, the fundus autofluorescence features, the thickened choroid, and also the small hyperreflective deposits on SD-OCT.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…6 On fundus examination, multiple discrete hypopigmented circular lesions over the posterior pole, the midperipheral retina, or around the optic disk were observed associated to multiple confluent hyperreflective deposits on SD-OCT in the different layers: RPE, the ellipsoid zone, and choroid. [6][7][8][9][10] Deferoxamine retinopathy and our case share some similarities: the RPE depigmentation, the fundus autofluorescence features, the thickened choroid, and also the small hyperreflective deposits on SD-OCT.…”
Section: Discussionmentioning
confidence: 65%
“…5 Besides iron overload, retinopathy induced by deferoxamine has been already described, including visual symptoms such as decreased visual acuity, night blindness, color vision abnormalities, cataract, optic neuropathy, and retinopathy. [6][7][8][9][10] Retinal abnormalities described in the literature were pigmentary degeneration in the macular equatorial regions, RPE atrophy, and bull's eye maculopathy. 6 On fundus examination, multiple discrete hypopigmented circular lesions over the posterior pole, the midperipheral retina, or around the optic disk were observed associated to multiple confluent hyperreflective deposits on SD-OCT in the different layers: RPE, the ellipsoid zone, and choroid.…”
Section: Discussionmentioning
confidence: 99%
“…Deferoxamine is a widely used chelating agent in treating transfusional hemochromatosis [1,5]. Visual symptoms included decreased visual acuity, night blindness, and colour vision abnormalities [2-6].…”
Section: Resultsmentioning
confidence: 99%
“…Rahi et al first reported electron microscopic findings of deferoxamine retinopathy, including patchy RPE depigmentation, abnormally thickened Bruch's membrane, and normal photoreceptors [9]. Previous studies also discovered that iron overload and iron-chelating agents both may be mutually confounding factors in the causation of ocular changes of thalassemia such as RPE mottling [5,10-13]. The SD-OCT findings in our case revealed multiple confluent hyper-reflective deposits in the RPE, IS/OS junction and choroid (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…1 Toxic retinopathy is one of the complications associated with deferoxamine, in which different manifestations including pigmentary retinopathy, bull's eye maculopathy, and vitelliform maculopathy have been described. [2][3][4][5][6][7][8] We report a patient who had rapid development of irreversible diffuse pigmentary retinopathy with severe visual loss while receiving continuous intravenous deferoxamine infusion.…”
Section: Rapid Development Of Severe Toxic Retinopathy Associated Witmentioning
confidence: 99%